Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Di Pasar Tradisional Aurduri Kota Jambi - Farhan Hamudi; Ahsan Putra Hafidz; Nova Erliyana (Jurnal Publikasi Manajemen Informatika, 2023)
This research is entitled Analysis of Factors that Influence Traders' Income in the Aurduri Traditional Market, Jambi City. This research has a problem formulation regarding what factors can influence income in the Aurduri traditional market, Jambi City. The factors are capital, working hours and experience. Then this research uses quantitative methods, the type of data used in this research is secondary data and primary data, the object of this research is the Aurduri traditional market in Jambi City with a sample of 74 vegetable traders. Next, data collection techniques are through interviews, questionnaires and documentation. The results of this research show that there is a partial influence of capital variables on traders' income at the Aurduri Traditional Market with the calculated t value > t table (2.218 > 1.994) and a significance value of 0.030 < 0.05, which means that Ho is rejected and Ha is accepted. In the working hours variable there is also a partial historical influence on the income of traders in the Traditional Market with the result of the calculated t value > t table (2.124 > 1.994) and a significance value of 0.037 > 0.05, which means that Ho is rejected and Ha is accepted. And for the last variable, namely the experience variable, there is also a partial influence on traders' income in the Traditional Market with the resulting value of t count > t table (4.283 > 1.994) and a significance value of 0.000 < 0.05, which means that Ho is rejected and Ha is accepted . So it can be concluded that there is a simultaneous influence between the variables of capital, working hours and experience on the income of traders at the Aurduri Traditional Market, Jambi City. Proven by the calculated f value > f table (16.427 > 3.13) and a significance value of 0.000 < 0.05 with a coefficient of determination (Adjusted R Square) of 53.9% while the remaining 46.1% is explained by other variables not examined in this research. So it can be concluded that Ha is accepted and Ho is rejected.